Metabolic responses of two pioneer wood decay fungi to diurnally cycling temperature. (12th July 2021) - Rawlings, Anna; O'Connor, Eoin; Moody, Suzy C.; Dudley, Ed; Boddy, Lynne; Fowler, Mike S.; Fitzpatrick, David A.; Doyle, Sean; Eastwood, Dan C.
Abstract: Decomposition of lignin‐rich wood by fungi drives nutrient recycling in woodland ecosystems. Fluctuating abiotic conditions are known to promote the functioning of ecological communities and ecosystems. In the context of wood decay, fluctuating temperature increases decomposition rates. Metabolomics, in tandem with other 'omics tools, can highlight the metabolic processes affected by experimental treatments, even in the absence of genome sequences and annotations. Globally, natural wood decay communities are dominated by the phylum Basidiomycota. We examined the metabolic responses of Mucidula mucida, a dominant constituent of pioneer communities in beech branches in British woodlands, and Exidia glandulosa, a stress‐selected constituent of the same communities, in response to constant and diurnally cycling temperature. We applied untargeted metabolomics and proteomics to beech wood blocks, colonised by M. mucida or E. glandulosa and exposed to either diurnally cycling (mean 15 ± 10°C) or constant (15°C) temperature, in a fully factorial design. Metabolites and proteins linked to lignin breakdown, the citric acid cycle, pentose phosphate pathway, carbohydrate metabolism, fatty acid metabolism and protein biosynthesis and turnover were under‐enriched in fluctuating, compared to stable temperatures, in the generalist M. mucida . Conversely, E. glandulosa showed little differential response to the experimental treatments. Synthesis . By demonstrating temperature‐dependant metabolic signatures related to nutrient acquisition in a generalist wood decay fungus, we provide new insights into how abiotic conditions can affect community‐mediated decomposition and carbon turnover in forests. We show that mechanisms underpinning important biogeochemical processes can be highlighted using untargeted metabolomics and proteomics in the absence of well‐annotated genomes. Abstract : Primary decay fungi in wood exposed to either stable (15°C) or diurnally cycling temperature regime (5–25°C; 10°C change every 6 hr) exhibit different proteomic and metabolic responses depending on whether they are characterised as stress adapted ( Exidia glandulosa ) or not ( Mucidula mucida ). E. glandulosa 's consistent expression of proteins and metabolites between incubation regimes contrasted with M. mucida 's more variable response under cycling incubation temperature.